Figurative Languages by the Lecturers in Teaching English at English Study Program of FKIP UKI Toraja - markus deli girik allo (Teaching English as a Foreign Language Overseas Journal, 2015)
The research aims at finding out (1) the kind of the Figurative Languages used by the lecturers (2) the ways of using Figurative Languages by the lectures (3) the reasons of using Figurative Languages by the lectures, and (4) the students’ perceptions toward the use of Figurative Languages by the lecturers. The researcher in this study employed the qualitative research design. The subjects of this research were Lecturers and students at English Education Study Program of FKIP UKI Toraja. The results of the research revealed that (1) the kinds of the Figurative Languages used by the lecturers are: Simile, metaphor, Personification, Rhetoric, Litotes, Paradox, Metonymy, Hyperbole, Repetition, (2) The ways of Using Figurative Languages by the lecturers are by making comparative, contradictive, correlative and repetitive statements that related to students’ life, culture and habit with the material in teaching English, (3) The reasons of using Figurative Languages are: Introducing language and culture, as a feedback to improve students’ understanding on the lessons, to help students’ understanding the lessons, to motivate students in learning process, enhancing the language (language style), and to train students’ critical thinking, and (4) The students’ perceptions toward the use of Figurative Language are: in association the material with the real world the students easily absorbed it because it was closer with their environment. The students who did not like and understand it because they needed the lecturers explained it directly the intended point.